Técnicas de Reforço Sísmico - Aníbal Costa (2008)
This chapter focuses on the description of severaltechniques used for reinforcing old masonry buildings of Faial Island, Azores, typically made of poor fabric and/or of regular block geometry. In first place the various causes of observed damage are described and analysed first as found in that island after the earthquake, leading to the identification of the main strengthening strategies. For each type of damage, a suitable solution is proposed, bearing in mind the two basic intervention lines related to damage of the whole structure and damage of structural parts or elements.